Cephalometric assessment of craniofacial dysmorphologies in relation with Msx2 mutations in mouse. (6th January 2014) - Simon, Y.; Marchadier, A.; Riviere, M. K.; Vandamme, K.; Koenig, F.; Lezot, F.; Trouve, A.; Benhamou, C. L.; Saffar, J. L.; Berdal, A.; Nefussi, J. R.
Structured Abstract Objectives To determine the role of Msx2 in craniofacial morphology and growth, we used a mouse model and performed a quantitative morphological characterization of the Msx2 −/− and the Msx2 +/− phenotype using a 2D cephalometric analysis applied on micrographs. Materials and Methods Forty‐four three‐and‐a‐half‐month‐old female CD1 mice were divided into the following three groups: Msx2 +/+ (n = 16), Msx2 +/− (n = 16), and Msx2 −/− (n = 12). Profile radiographs were scanned. Modified cephalometric analysis was performed to compare the three groups. Results Compared with the wild‐type mice, the Msx2 −/− mutant mice presented an overall craniofacial size decrease and modifications of the shape of the different parts of the craniofacial skeleton, namely the neurocranium, the viscerocranium, the mandible, and the teeth. In particular, dysmorphologies were seen in the cochlear apparatus and the teeth (taurodontism, reduced incisor curvature). Finally contrary to previous published results, we were able to record a specific phenotype of the Msx2 +/− mice with this methodology. This Msx2 +/− mouse phenotype was not intermediate between the Msx2 −/− and the wild‐type animals. Conclusion Msx2 plays an important role in craniofacial morphogenesis and growth because almost all craniofacial structures were affected in the Msx2−/− mice including both intramembranous and endochondral bones, the cochlear apparatus, and the teeth. In addition, Msx2 haploinsufficiency involves a specific phenotype with subtle craniofacial structures modifications compared with human mutations.